Effect of Puncture Tapping Systems on Yield and Selected Physiological Latex Parameters of Rubber (Hevea Brasiliensis Muell. Arg.) - Arroyo, Salvador Ruiz (1996)
These studies were carried out to evaluate the effect of puncture tapping system on yield performance of clone RRIM 600 and PR 261 and selected physiological latex parameters of clone RRlM 600. Three main experiments were carried out. The first and second experiments studied the effect of number of punctures, puncture strips and times of tapping on yield performance of clones RRIM 600 and PR 261 during the last five and six years respectively. The third experiment studied the effect of number of puncture strips and panel position on yield as well as on selected physiological latex parameters of RRIM 600 over one year duration. The rubber yield of clones RRIM 600 and PR 261 was not affected by the number of punctures (3, 6, 9 and 12), puncture strips (single and triple) and times of tapping (7:00,9:00, 11:00 am and 1:00 pm). However the yield of puncture tapped trees was comparable to that of 1I2S d/2 tapped excision unstimulated control. Yield performance of clone RRIM 600 was also not affected by either high or low panel position. All puncture tapped trees with three strips produced similar yield as 1I2S d/2 tapped unstimulated control. Among the physiological latex parameters related to latex flow affected by puncture tapping system were bottom fraction (BF) and thiol (RS-H), while no significant effects were noted on bursting index (BI) and dry rubber content (DRC). Trees puncture tapped with three strips on high panels HO-l and HO-2 recorded the highest percentage of BF while trees puncture tapped with single strip on panel BO-2 recorded the lowest percentage of BF. However puncture tapping treatments did not result in higher percentage of BF than 1I2S d/2 and 1I4S t d/2 tapped unstimulated controls. Among puncture tapped trees the highest RS-H was recorded with three strips tapped on panel BO-2. The other puncture tapped treatments recorded similar RS-H to that of 1/2S d/2 and 1I4S t d/2 tapped unstimulated controls.